The Impact of Foreign Tourists on the Culture of the Sasak Community in Ende Tourism Village, Central Lombok Regency - Pikrianto; Wahyu Khalik; Muhamad Johari (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to analyse The Impact of Foreign Tourists on the Culture of the Sasak Community in Ende Tourism Village, Central Lombok Regency. The focus of the study is on how tourist interactions influence traditional values, cultural practices, and the adaptation patterns of the Sasak community in facing the development of global tourism. Method: This study uses a qualitative method with a descriptive approach. Data were obtained through observation, unstructured interviews, and documentation. Research informants included community leaders, tourism village managers (POKDARWIS), and local communities directly involved in tourism activities. Data analysis used Miles and Huberman's interactive model, which includes the stages of reduction, presentation, and conclusion drawing. Result: The results of the study show that tourism has a positive impact on economic growth, job creation, and public awareness of the importance of preserving local culture. But the commodification of culture, like the conversion of Peresean and Gendang Beleq arts into tourist attractions, has changed the meaning of tradition. The Sasak community has demonstrated selective adaptation by preserving traditional architecture, social values, and local language, while also adopting elements of modernity through foreign language proficiency and creative economic innovation. Contribution: This study contributes to the development of culture-based tourism in Indonesia by emphasising the importance of balancing economic benefits and the preservation of local values. The results of this study also serve as a reference for local governments, tourism village managers, and academics in designing sustainable tourism management strategies that preserve the cultural identity of local communities.